EFEKTIVITAS IMPLEMENTASI PROGRAM 5S (SEIRI, SEITON, SEISO, SEIKETSU, SHITSUKE) DI PT PJB UP GRESIK - andika prastiya (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The purpose of this research was to investigated how differences in the effectiveness and implementation of 5S in PT Pembangkitan Jawa Bali Unit Pembangkitan (PJB UP) Gresik, used descriptive analysis and test tool cocrhan test. The company had implemented 5S program since 2010, and so far has gone well, so darting through the appropriate used for an object of this study.The results showed that the implementation of 5S in PT PJB UP Gresik was very satisfying, almost all had done in each area in PT PJB UP Gresik and this was evidenced from the responsible answer to the claim area of each part in the company area. Of the five items that Seiri, Seiton, Seiso, Seiketsu, and Shitsuke also obtained the result that there was no difference in the effectiveness of the implementation of 5S significant in PT PJB UP Gresik. This can be seen from test results that showed the test Cochran Cochran calculated value was smaller than the value of Chi Square Table 0444 <9:49, which means the same or different in the running application.